UTILIZATION OF DIGITAL TOOLS IN TEACHING AND LEARNING OF BIOLOGY IN SENIOR SECONDARY SCHOOLS IN ABUJA MUNICIPAL AREA COUNCIL, FEDERAL CAPITAL TERRITORY, ABUJA - Egbunu , Roseline (Journal of Continuing and Development Education, 2024)
The study investigated the utilization of digital tools in teaching and learning of Biology in senior secondary schools in Abuja Municipal Area Council, Federal Capital Territory. Two research objectives and two research questions guided the study. The study adopted descriptive survey research design. The target population was all the 54 Biology teachers in all the 18 public senior secondary schools in Abuja Municipal Area Council (AMAC). The entire population constituted the sample for the study, adopting census sampling technique. Thirteen (13) items self-structured questionnaire tiled: “Utilization of Digital Tools in Teaching and Learning of Biology Questionnaire (UDTTLBQ) was used to generate data for the study. Testretest method of reliability was used to obtain the internal consistency. The reliability index was obtained through Cornbrash’s alpha (0.98). Out of the 54 questionnaires administered, 51 were returned valid, representing 94% success rate. Data collected was analysed using descriptive statistics, in the form of frequency tables and graphs. The results revealed that Google search engine and Wikipedia are major digital tools that Biology teachers utilize to facilitate the teaching and learning of Biology. Majority of Biology teachers are particularly unaware of Padlet, Socrative and Notability digital tools. Also, high cost of internet subscription and slow internet speed are major constraints to the utilization of digital tools for teaching and learning of Biology in secondary schools in Abuja Municipal Area Council. It was recommended among others that Biology teachers should go for professional courses, workshops and training on ICT particularly on how to use digital tools such as Padlet, Socrative and Notability to facilitate the teaching and learning of Biology and Biology teachers should constantly update their knowledge on new trends in digital tools that can make their teaching interesting and understandable for students.